Methods of inspection of flat-valgus deformation of foot in the conditions of a specialized preschool institution or at home - Prysyazhnyuk, Ulyana; Vovkanych, Andriy (The Ukrainian Scientific Medical Youth Journal, 2022)
during the first years of a child’s life, he grows intensively, perceives and learns about the world around him, all the systems of his child’s body are actively developing, in particular, it is worth noting the muscular and bone systems that form the musculoskeletal system of a person. Diseases of the musculoskeletal system (MSD) are among the most common in children of preschool and primary school age. The main factor affecting the development of ORA pathologies can be considered the weakness of the muscular system, since muscles at this age are characterized by a high ability to stretch and do not provide reliable fixation of bones. The bones themselves are characterized by less hardness and greater plasticity than the bones of adults, they are more easily deformed under the influence of external factors. As a result, we quite often have the opportunity to observe acquired pathologies of the musculoskeletal system in preschool children, such as clubfoot, x-shaped feet, flat feet, flat-valgus or varus foot deformity. In turn, diseases of the lower extremities provoke diseases of the spine, in particular, postural disorders and their varieties. In order to timely detect the manifestations of diseases of the lower extremities, it is important to be able to conduct an examination and analyze it correctly. The purpose of this article is to highlight the methods of examining the feet of preschool children, which are easy to perform, and also possible to use at home or in the conditions of a specialized preschool institution. Research methods: analysis and generalization of data from scientific and educational and methodological literature regarding the main diseases of the lower extremities, methods of their examination and methods of conducting these examinations in the conditions of specialized preschool institutions or at home. The obtained results - based on the analysis of the main methods of foot examination, those of them were selected, which, on the one hand, are quite easy to implement in practice in a specialized children’s preschool or at home, which do not require the presence of complex and expensive equipment, and can also be carried out independently by employee’s institution of preschool education, and, on the other hand, ensure the proper validity of the obtained results. The practical significance of the scientific work is that the algorithm for carrying out and evaluating the obtained data is prescribed, which can be applied in the conditions of a specialized preschool institution or at home (Friedland’s pedometric index using a compass and a ruler; contourography; measurement of the volume of the feet). Their application enables in digital format or visually the results of a physical therapy program for the treatment of flat-valgus deformity of the feet. It is no less important that these methods can be used in the form of a game, which is an important factor for examining children, especially preschoolers